Robotic intraoperative tracheal repair during retrosternal malignant goiter excision: an anesthetic challenge - Verma, Ankur; Biswas, Shubhashish; Singh, Pooja; Tyagi, Tarun; Khatri, Pankaj; Gupta, Tushar; Dabas, Surender Kumar (International Journal of Research in Medical Sciences, 2023)
Thyroidectomy is the treatment of choice for large retrosternal goiters. These tumors often are large enough to require thoracotomy. Robotic surgery can help in avoiding thoracotomy and its associated post operative complications. Rarely, such tumors and their surgery can be complicated by tracheal tears. Such tears, especially those near the carina are difficult to repair and often require open thoracotomy. We described such a case where we avoided open thoracotomy and instead performed a minimally invasive robotic repair of tracheal tear. The maintenance of ventilation during this robotic repair was critical. A combination of several airway devices was used to allow the complex surgical repair to be executed without affecting ventilation.